Evaluation of frozen bull semen. Quick and slow thermoresistance tests: effects on fertility - Arruda, Rubens Paes de; Barnabe, Valquíria Hyppolito; Alencar, Mauricio Mello de; Barnabe, Renato Campanarut (Brazilian Journal of Veterinary Research and Animal Science, 1992)
It was studied the effect of frozen bull semen after thawing and incubation at 45 °C during one hour or at 38 °C during 5 hours (Quick and Slow Thermoresistance Tests), on fertility of beef cows. Treatment 1 included 6 groups of 10 females inseminated with semen showing 20% or plus of progressive motility on quick test and less than 20% on slow test. Treatment 2 (control) included 5 groups of 10 and 1 group of 9 females inseminated with semen showing 20% of progressive motility on slow test and any value on quick test. Only one straw was utilized per estrus, admitted up to 3 repetitions. Pregnancy diagnosis was made by rectal palpation, 60 days after A.I.. Satisfactory results in pregnancy rates were obtained in both treatments (QTT/Q = 0.793 + ou - 0.05 and STT/S = 0.875 + ou - 0.05) with no statistical differences (P>0.05) between them. There was no statistical differences in pregnancy rates of cows inseminated with semen showing motility from 20 to 50% after incubation at 45 °C for one hour.